Overview of the Source of Covid-19 Infection in H. Andi Sulthan Daeng Radja Hospital nurses in 2020 - Sitti Rahmawati; Asnidar; Hasriani; Erwa Nurwaji; Nurawaliyah Rasyid (Comprehensive Health Care, 2022)
Corona Virus Disease-19 (Covid-19) is an infectious disease caused by the SARS- CoV 2 virus or corona virus. Until now, the number of nurses who were exposed to COVID-19 continued to increase. Nurses as the front line in handling COVID- 19 have a vulnerability to exposure. This study aims to describe the possible sources of Covid-19 infection in nurses at RSUD H. Andi Sulthan Daeng Radja during 2020. The research design was descriptive, the number of samples was 32, the sampling technique was total sampling. Data analysis is frequency distribution and percentage. The results showed that most of the 22 people (68.75%) the source of exposure to covid 19 in nurses were colleagues.